The clinical influence of nasal surgery on PAP compliance and optimal application among OSA subjects uncomfortable with PAP device wear - Cha, Hyunkyung; Oh, Heonjeong; Han, Sun A; Kim, Seo Young; Kim, Jeong Kyou; Park, Hae Chan; Han, Doo Hee; Kim, Dong-Young; Kim, Hyun Jik (Scientific reports, 2023)
This study aimed to evaluate the alteration of PAP compliance after nasal surgery and to determine the optimal indications of nasal surgery in obstructive sleep apnea (OSA) subjects. Among OSA subjects using PAP devices, 29 subjects who underwent septoturbinoplasty due to nasal obstruction were included and their pre- and postoperative medical and PAP records were reviewed retrospectively. Postoperative autoPAP usage data was further assessed by grouping the compliance (the percentage of days with usage ≥ 4 h) data (group 1: the good compliance group; group 2: the poor compliance group). The data showed that 56% of subjects in group 1 complained of nasal obstruction as the only barrier to using a PAP device and about 89% reported experiencing the efficacy of PAP usage. Both the mean and peak average PAP pressures were significantly reduced in group 1 following nasal surgery. Group 2 had multiple subjective problems that interfered with wearing a PAP device and reported a lack of experiencing the efficacy of PAP usage. Preoperative nasal cavity volume values were smaller and absolute blood eosinophil counts were significantly lower in group 1. The current data demonstrate that nasal surgery might increase the compliance of PAP device wear in OSA subjects who complained of only nasal obstruction as a barrier to wearing PAP and who had small nasal cavity volumes combined with allergic inflammation.